Associations of Preimplant Red Blood Cell Distribution Width with Clinical Outcomes Among Individuals with Left Ventricular Assist Devices. Issue 6 (November 2016) - Miller, P. Elliott; Houston, Brian A.; Schneider, Andrea L. C.; Bush, Aaron L.; Whitman, Glenn J.; Stevens, Gerin R.; Tedford, Ryan J.; Russell, Stuart D.
Abstract : Left ventricular assist devices (LVADs) are increasingly used for end-stage heart failure. However, post-LVAD complications are potentially devastating and remain unpredictable. The red blood cell distribution width (RDW) is a predictor of adverse events in patients with heart failure but has not been studied in the LVAD population. We reviewed laboratory results and clinical outcomes for all continuous flow LVADs implanted from 2004 to June 2014 (N = 188). Cox proportional hazards models adjusted for demographic, cardiovascular, and laboratory variables were used to assess association of preimplant RDW tertiles with mortality, gastrointestinal bleed, infection, pump thrombosis, and stroke more than 1 year of follow-up. Compared with the lowest tertile (RDW < 15.7%), the higher two tertiles (RDW 15.7–18% and RDW >18.1%) had significantly higher risks of mortality (hazard ratio (HR) 6.95 [confidence interval: 2.67–18.10] and HR 4.61 [1.74–12.21], respectively) after full adjustment. Preimplant RDW was not statistically associated with our secondary outcomes. In conclusion, higher preimplant RDW is independently associated with an increased risk of postimplant mortality and infection. Future studies are needed to understand the prognostic ability of RDW and to understand the biologic mechanism underlying this association.